Perceived discrimination among Syrian refugees in Germany and its associations with mental health - Viazminsky, Andre; Borho, Andrea; Morawa, Eva; Schmitt, Gregor Martin; Erim, Yesim (Global Public Health, 2022)
Discrimination is a crucial post migratory stressor but there is little research on perceived discrimination by Syrian refugees. This study aims to assess self-reported discrimination by Syrian refugees with a residence permit in Germany, determine its forms, places, and predictors, and explore its possible relation with mental health. Sociodemographics, migration-specific characteristics, traumatic life events, quality of life, perceived discrimination, depression, generalised anxiety disorder, post-traumatic symptoms, and somatic distress were assessed among 116 participants. More than one-third of the participants perceived discrimination in low frequency, and in general, perceived discrimination was confined to treatment with less courtesy or respect. Unfair treatment was perceived mostly while searching for accommodation and in the neighbourhood. Refugees attributed their experiences to their lack of language skills prior to national, religious, and racial causes. Lower age, higher number of completed years of education, and symptoms of posttraumatic stress disorder were significantly and substantially associated with perceived discrimination. Anxiety symptoms, number of traumatic experiences and gender may also be regarded as relevant predictors of perceived discrimination. Health care professionals must be aware of the links between discrimination and symptoms of mental disorders. Policymakers should address discrimination as a key refugee issue and risk to mental health.
CRIS-Team WoS Importer:2022-01-28